Letters and telegrams mostly to John Redmond regarding the 'Freeman's Journal', with copies of replies from Redmond, - Redmond, John Edward, 1856-1918 (1912)
Correspondents include Stephen O'Mara, John Dillon, William H. Brayden, Daniel Purcell, Matthew J. Minch, John Muldoon, and J. J. Hanna.